Efficacy of Possum in Surgical Audit of Patient Undergoing Emergency Surgery at Nepalgunj Medical College - Bharti, S V; Mishra, S M; Ranjitkar, R R; Chhetri, A O (Journal of Nepalgunj Medical College, 2018)
Introduction: The Physiological and Operative Severity Score for the en Umeration of Mortality and morbidity (POSSUM) has been proposed as a method for standardizing patient data so that direct comparisons can be made in spite of differing patterns of referral and population.Aims and objectives: To evaluate the efficacy of a scoring system for predicting the incidence of postoperative complications and mortality in patient undergoing Emergency Surgeries based on the Physiological and Operative Severity Score for the Enumeration of Mortality and Morbidity (POSSUM).Material and Methods: This is a hospital based cross sectional study of all the cases that had undergone Emergency Surgery at Nepalgunj Medical College Teaching Hospital from the period of July 2014 to June 2015. The period of follow up was 30 days following the surgical procedure? A total of 100 emergency surgeries, as defined by the POSSUM scoring system criteria were studied. Predicted mortality and morbidity rates were calculated using the POSSUM equation by exponential analysis method. It was then compared with the actual outcomes. Observed: Expected Ratio (O:E) was calculated and difference detected by chi-square test. The risk factors as scored in the POSSUM criteria were noted.Results: Applying exponential analysis, an observed to expected ratio (O:E) for mortality of 0.44 was obtained, indicating significant 2 difference between the predicted and observed values (x =93.207, df 63, p=0.008). But, an observed to expected ratio (O:E) for 2 morbidity of 1.01 was obtained and there was no significant difference between the predicted and observed values (x =76.295, df 71, p=0.312). It was found to be comparable to other studies. In all the risk factors studied, a positive correlation was found between deaths and post-operative complications with higher POSSUM scores.Conclusion: POSSUM scoring system could accurately predict overall morbidity while it over predicted the overall mortality. POSSUM scoring system serves as a good predictor of post-operative outcome in major general surgical procedures and was applicable even in our setup and be used for comparing various treatment modalities and assessing the quality of care provided. JNGMC Vol. 14 No. 2 December 2016,   page: 2-7